Women's suffrage : fighting for women's rights - Isecke, Harriet (Huntington Beach, CA : Teacher Created Materials, 2012)
The fight to change the law to allow women to vote was called the Suffrage Movement. Those who joined this fight were called suffragists. Many brave suffragists organized groups, gave speeches, and held marches and parades. It took women almost 150 years to get the right to vote. This is the story of how they did it.
Includes index.
Keywords: Women -- Suffrage -- United States -- History -- Juvenile literature; Feminists -- United States -- Biography -- Juvenile literature; Women -- Political activity -- United States -- History -- Juvenile literature; Women -- Suffrage -- History; Feminists -- United States; Women -- Political activity -- History; Feminists; Women -- Political activity; Women -- Suffrage; United States; Women -- Suffrage; Feminists; Biography; History; Juvenile works